New species and records in Phrynidius Lacordaire (Coleoptera, Cerambycidae, Lamiinae) - Noguera, Felipe A.; Santos-Silva, Antonio (Zootaxa, 2023)
Phrynidius Lacordaire, 1869, a genus of Mesoamerican distribution, is a group whose original taxonomic knowledge was generally limited, mainly due to the original descriptions not allowing for the adequate determination of its species. Recently, this knowledge was increased with the description of new species and the publication of a key to separate them. However, this knowledge is still incomplete, and there remain undescribed species deposited in different entomological collections. In this study, we update the taxonomic and distributional knowledge of the genus, and provide a new key to separate the species. Seven new species are described: P. poriferus sp. nov., from Honduras; P. skillmani sp. nov., from Guatemala; P. obrieni sp. nov., from Honduras; P. wibmeri sp. nov., from Mexico; P. pallifemoralis sp. nov., from Mexico; P. oaxacanensis sp. nov., from Mexico; P. guatemalensis sp. nov., from Guatemala. Phrynidius echinus Bates, 1880 is briefly redescribed and reported for the first time for the Guatemalan department of El Progreso. Phrynidius armatus Linsley, 1933 is excluded from the Nicaraguan fauna. Additionally, two new country records are reported: Phrynidius guifarroi Santos-Silva, Van Roie & Jocqué, 2021, from Guatemala; and P. nayaritensis Heffern, Nascimento & Santos-Silva, 2018, from Honduras.